Pro-inflammatory granzyme K contributes extracellularly to disease - Turner, Christopher T. (Frontiers in Immunology, 2025)
Granzyme K (GzmK) is an immune-secreted serine protease typically expressed at low levels but elevated in response to tissue injury and disease. Known as an orphan granzyme due to limited scientific investigation, this tryptase is being redefined as having important roles in inflammation and disease pathogenesis. Multiple GzmK expressing CD8+ T cell subsets are being identified with augmented expression and important roles in disease. Traditionally recognized as a mediator of cytotoxic lymphocyte-mediated cell death, GzmK’s role is being recharacterized through multiple recently released studies focused on newly identified extracellular mechanisms of action. These studies identify GzmK to be inflammatory, being able to trigger pro-inflammatory cytokine release, enhance immune cell recruitment, exacerbate the immune response to bacterial infections, and activate complement. In multiple disease states, dysregulated GzmK expression and potential accumulation in the extracellular space directly contributes to impaired health outcomes, thereby suggesting downregulation may prevent disease severity. GzmK is therefore emerging as a therapeutic target, potentially valuable in sepsis, pulmonary disease, inflammatory skin disease, rheumatoid arthritis and even aging.